Reservoir Hydrocarbon Volumetric Analysis of Sapele Deep Field, Niger Delta, Southern Nigeria - Airen, O. J.; Mujakperuo, B. J. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The calculation of hydrocarbon volume in place of Sapele Deep field in the Niger Delta, Nigeria was done by the integration of seismic and well logs data using the petrel software. On average, the entire field has a hydrocarbon pore volume of 90,341.68, STOIIP value of 1,156,970,604.11 BBCF/BBSTB and an ultimate recovery value of 951,966,117.95 MMCF/MMSTB with a primary recovery factor of 0.81 (81%). Petrophysical evaluation reveals that the field on average, has a gross thickness of 268.60m (886.38 ft), net sand thickness of 6.67 m (22.01 ft), porosity value of 0.21 (21%), permeability of 1493.14 mD, shale volume of 0.16, net-to-gross value of 0.51 and water saturation (Sw) of 0.43 (43%). The combination of well log neutron and density log reveals that the study area is made up of both single and double-phase reservoirs.